2011
DOI: 10.1111/j.1750-2659.2011.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of a link between influenza vaccines and Guillain–Barre syndrome–associated antiganglioside antibodies

Abstract: Please cite this paper as: Wang et al. (2011) No evidence of a link between influenza vaccines and Guillain–Barre syndrome–associated antiganglioside antibodies. Influenza and Other Respiratory Viruses 6(3), 159–166. Background  Guillain–Barre syndrome (GBS) is a rare autoimmune disease characterized by acute, progressive peripheral neuropathy and is commonly associated with the presence of antiganglioside antibodies. Previously, influenza vaccination was linked with the increased incidence of GBS; however, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…Although anti-ganglioside antibodies can recognize the influenza virus (probably due to glycosylation), no such antibodies were found in sera of vaccinated patients [77]. Although no studies have identified specific T cell epitopes involved, it is clear that their formation is T cell-dependent.…”
Section:  Guillain-barré Syndromementioning
confidence: 99%
“…Although anti-ganglioside antibodies can recognize the influenza virus (probably due to glycosylation), no such antibodies were found in sera of vaccinated patients [77]. Although no studies have identified specific T cell epitopes involved, it is clear that their formation is T cell-dependent.…”
Section:  Guillain-barré Syndromementioning
confidence: 99%
“…Wang et al found GM1 and GM2 antiganglioside polyclonal antibodies cross-react with multiple H1N1 and H3N2 influenza strains based on the degree of virus glycosylation [15]. They also followed-up (in 2009) 46 persons previously vaccinated with 1976 H1N1 influenza vaccine and did not find anti-GM1, -GM2 or -GD1a antibodies in their serum.…”
Section: Neal a Halseymentioning
confidence: 99%
“…However, among 612 recipients of 2007-2008 or 2008-2009 influenza vaccines, 4 (all >60 years of age) had detectable antiganglioside antibody after immunization. They also injected mice with influenza vaccine and found the ability to induce antiganglioside antibodies varied by the strains of mice, suggesting a genetic role [15]. One small study failed to detect antiganglioside antibodies in 6 mice, 8 GBS patients or 60 other humans who had received the 2009 H1N1 vaccine [16].…”
Section: Neal a Halseymentioning
confidence: 99%
“…After detection of the virus, vaccine manufacturers started developing a pandemic H1N1 vaccine. Global vaccinations inoculated against swine flu with the use of inactivated, without and with adjuvant, and live attenuated vaccines [8][9][10][11]. Healthcare workers were among the first to be inoculated against swine flu in most countries, including Turkey.…”
Section: Introductionmentioning
confidence: 99%